Dantrolene-Induced Hepatitis: A Rare Culprit in the PICU - Pasrija, Divij; Gupta, Shilpi; Hassinger, Amanda (Journal of Pediatric Intensive Care, 2020)
Dantrolene is used for reversal of malignant hyperthermia and for improvement in spasticity following stroke which are Food and Drug Administration-approved indications. It is an infrequently used medication in the pediatric intensive care unit and is usually continued from the operating room or sedation suite after suspicion for malignant hyperthermia, secondary to other medications and anesthetic agents. Hepatitis has been described as a side effect of the medication after prolonged use and at doses of more than 100 mg/d mainly in adults. We described in this case report a patient in which the drug was used for sympathetic overactivity in the PICU and development of asymptomatic hepatitis on day 3 after starting the medication at a dose much lower than previously described.
Keywords: dantrolene; spasticity; hepatitis; toxicity